(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Brainstem death and Halachà are compatible? The article reviews the most relevant literature on the subject in order to ascertain whether Jewish Law can adopt brainstem death as a criterion to declare a patient’s death. The conclusion is that there is not a shared consensus in the Jewish law, even though brainstem death has be recognized by important auctoritates, among them the Chief Rabbinate of Israel, as valid for Jewish law.